Hubungan Tata Kelola, Pelaporan, Kelangsungan Usaha, dan Kepercayaan Investor Pada Sektor Perbankan - Dewi Lestari; Rita Wijayanti (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This research aims to analyze the relationship among corporate governance, corporate reporting, going concern, and investor confidence in financial sector companies listed on the Indonesia Stock Exchange during the period 2019–2021. The data were processed using the Statistical Package for the Social Sciences (SPSS) version 25.0. This study uses secondary data obtained from companies’ annual financial reports. The sampling technique employed is purposive sampling, with a total of 41 companies meeting the criteria as observation units. The analytical methods include descriptive statistical analysis, classical assumption tests, multiple linear regression, model feasibility tests, and hypothesis testing. The results show that the variable of going concern has a significant influence on investor confidence, and corporate governance directly affects investor confidence. However, corporate reporting does not have a direct effect on investor confidence. Furthermore, corporate governance indirectly influences investor confidence through the mediation of going concern, while corporate reporting does not have an indirect effect on investor confidence through the same mediation.